Examine The Influence Of Green Human Resource Management On Environmental Performance: Mediating Role Of Organizational Focused Citizenship Behaviour Towards The Environment - GILL, DR. ATIF ALI; ANSARI, RIAZ HUSSAIN; MALIK, SAMRA; AKHTAR, NASREEN (The journal of contemporary issues in business and government, 2021)
The awareness about environmental concerns in organizations has been increased in recent research. Green human resources are becoming a crucial element to implement green practices in organizations. Limited research in the context of the inefficient environmental performance of universities is drawing the attention of scholars. Based on the Ability - Motivation-Opportunity (AMO) theory, the current study examines the indirect effect of GHRM practices on universities' environmental performance through organizational citizenship behavior toward the environment. The survey method was used for data collection from the academic staff of public sector universities in Punjab, Pakistan. Convenience sampling was used, and a partial least square structural equation modeling technique was used to analyze the data statistically. Direct hypothesis results revealed the significant impact of green performance, green reward, and green training on the environment's organizational citizenship behavior. The environment's organizational citizenship behavior significantly mediates the relationship between green performance, green reward, and green training and environmental performance for mediation analysis. The study findings provide numerous theoretical and practical implications by extending the AMO theory and guiding universities' administration to train the academic staff and increase the reward to improve public sector universities' environmental performance.